BAFF regulates activation of self‐reactive T cells through B‐cell dependent mechanisms and mediates protection in NOD mice. Issue 4 (16th February 2014) - Mariño, Eliana; Walters, Stacey N.; Villanueva, Jeanette E.; Richards, James L.; Mackay, Charles R.; Grey, Shane T.
<x xml:space="preserve">Abstract</x> Targeting the BAFF/APRIL system has shown to be effective in preventing T‐cell dependent autoimmune disease in the NOD mouse, a spontaneous model of type 1 diabetes. In this study we generated BAFF‐deficient NOD mice to examine how BAFF availability would influence T‐cell responses in vivo and the development of spontaneous diabetes. BAFF‐deficient NOD mice which lack mature B cells, were protected from diabetes and showed delayed rejection of an allogeneic islet graft. Diabetes protection correlated with a failure to expand pathogenic IGRP‐reactive CD8+ T cells, which were maintained in the periphery at correspondingly low levels. Adoptive transfer of IGRP‐reactive CD8+ T cells with B cells into BAFF‐deficient NOD mice enhanced IGRP‐reactive CD8+ T‐cell expansion. Furthermore, when provoked with cyclophosphamide, or transferred to a secondary lymphopenic host, the latent pool of self‐reactive T cells resident in BAFF‐deficient NOD mice could elicit beta cell destruction. We conclude that lack of BAFF prevents the procurement of B‐cell‐dependent help necessary for the emergence of destructive diabetes. Indeed, treatment of NOD mice with the BAFF‐blocking compound, BR3‐Fc, resulted in a delayed onset and reduced incidence of diabetes.